Data harmonization and data pooling from cohort studies: a practical approach for data management. (2021) - Adhikari, Kamala; Patten, Scott B; Patel, Alka B; Premji, Shahirose; Tough, Suzanne; Letourneau, Nicole; Giesbrecht, Gerald; Metcalfe, Amy
No abstract available